Optimizing Village Tourism Businesses with the Business Model Canvas: A Strategic Approach - ANGGRAINI, Ni Putu Nita; MITARIANI, Ni Wayan Eka; IMBAYANI, I Gusti Ayu; PRAMUDIAH, Desak Dwita Amanda; YANI, Luh Komang (Journal of Entrepreneurial and Business Diversity, 2024)
Purpose:Local wisdom-based tourism has become a prominent trend as it provides authentic experiences for tourists while supporting environmental and cultural sustainability. This study aims to optimize the management of Munggu Tourism Village, Bali, by implementing the Business Model Canvas (BMC). Munggu Tourism Village holds rich tourism potential, including the Mekotek tradition, natural landscapes, traditional cuisine, and arts.Methodology:The research employs a qualitative approach, utilizing observation, in-depth interviews, and Focus Group Discussions (FGD) involving key stakeholders, such as village officials, traditional leaders, and local entrepreneurs. The findings reveal that the application of BMC facilitates mapping the nine essential elements of a business model, such as customer segments, value propositions, and distribution channels.Findings:This study offers practical contributions to the development of local wisdom-based tourism and serves as a strategic guide for creating leading tourism destinations. The theoretical implications include flexibility in long-term business planning and the ease of updating business models to adapt to market dynamics. Future research is recommended to apply BMC to tourism villages operating for over a year to evaluate its long-term impact.Implication: This study confirms that the Business Model Canvas BMC is a strategic tool that effectively supports the sustainable development of tourism villages based on local wisdom. The findings provide practical guidance for tourism village managers and government authorities in designing effective business strategies, empowering local communities, and maintaining the attractions of the destination,